Environmental Science Communication for a Young Audience: A Case Study on the #EarthOvershootDay Campaign on YouTube - Kaul, Lena; Schrögel, Philipp; Humm, Christian (Frontiers in Communication, 2020)
Addressing global sustainability challenges such as climate change requires thorough political and societal debates and following decisions in democratic societies. Science and environmental communication is needed to inform these debates. However, not all parts of society are equally reached by traditional science communication. In particular young people, especially without academic background, are often left out. The cooperation of science communicators with influencers on the video platform YouTube can be a way to convey scientific information and raise awareness for environmental issues with new young audiences. This case study looks at three videos from the campaign #EarthOvershootDay on YouTube by the WWF (World Wide Fund for Nature) Germany and the educational initiative MESH Collective. The focus of the analysis lies on the established success factors of communication through influencers – specifically authenticity, comprehensibility and storytelling – and how they play out in detail in the three exemplary videos. Besides the analysis of the videos, the study is corroborated by interviews with the producers and a comment analysis in order to include the perspective of the viewers. Our analysis confirms previous findings on science communication with influencers and illustrates the aspects in their concrete implementation. It shows that authenticity is a central aspect which is not disturbed through the presentation of scientific content. The storytelling approaches are tailored to the respective influencer and their style. The language and structure of the videos are simple and comprehensible, scientific arguments focus on selected aspects and are tied to examples from everyday life. The comments by the users support these findings with the majority of comments addressing the three aspects of our analysis being positive. However, evidence for an in-depth engagement with the scientific contents could not be found in the comments. The stated goal of the campaign to reach educationally disadvantaged young people was only reached to a limited degree according to the assessment of the producers. Additionally, the views of two of the three videos remained below the average for the respective channel. Taken together this indicates that cooperation with influencers might not be an “all-purpose weapon” guaranteeing success for science communication.